EyeFrame: Real-Time Memory Aid Improves Human Multitasking via Domain-General Eye Tracking Procedures - Taylor, P.; Bilgrien, Noah; He, Ze; Siegelmann, Hava T. (Frontiers in ICT, 2015)
OBJECTIVE: We developed an extensively general closed-loop system to improve human interaction in various multitasking scenarios, with semi-autonomous agents, processes, and robots. BACKGROUND: Much technology is converging toward semi-independent processes with intermittent human supervision distributed over multiple computerized agents. Human operators multitask notoriously poorly, in part due to cognitive load and limited working memory. To multitask optimally, users must remember task order, e.g., the most neglected task, since longer times not monitoring an element indicates greater probability of need for user input. The secondary task of monitoring attention history over multiple spatial tasks requires similar cognitive resources as primary tasks themselves. Humans can not reliably make more than ~2 decisions/s. METHODS: Participants managed a range of 4-10 semi-autonomous agents performing rescue tasks. To optimize monitoring and controlling multiple agents, we created an automated short term memory aid, providing visual cues from users' gaze history. Cues indicated when and where to look next, and were derived from an inverse of eye fixation recency. RESULTS: Contingent eye tracking algorithms drastically improved operator performance, increasing multitasking capacity. The gaze aid reduced biases, and reduced cognitive load, measured by smaller pupil dilation. CONCLUSIONS: Our eye aid likely helped by delegating short-term memory to the computer, and by reducing decision making load. Past studies used eye position for gaze-aware control and interactive updating of displays in application-specific scenarios, but ours is the first to successfully implement domain-general algorithms. Procedures should generalize well to: process control, factory operations, robot control, surveillance, aviation, air traffic control, driving, military, mobile search and rescue, and many tasks where probability of utility is predicted by duration since last attention to a task.